ANALISIS MARGIN PEMASARAN TELUR AYAM RAS PADA USAHA PETERNAKAN âCAHAYA ARIS MANISâ DI DESA LANGALESO KECAMATAN DOLO KABUPATEN SIGI - Fadil, Muh; Kalaba, Yulianti; Kalaba, Yulianti; Muiis, abdul (AGROTEKBIS, 2017)
The purpose of the study was to determine the marketing channels, marketing margin, Â Â Â Â part of the price received by farmers and marketing efficiency. Determination of the respondents to the farm was done intentionally (purposive). Total respondents two people consisting of 1 leader and 1 employee with the consideration that the respondents have to know the flow of the marketing of the products produced. Respondent traders used assessment method (Tracing Method), in order to obtain each 2 collectors and 1 retailers. The results showed that there are two channels of marketing eggs in the effort